Society, Environment and Human Security in the Arctic Barents Region - Hossain, Kamrul; Cambou, Dorothée (Routledge, 2020)
This title is published in Open Access with the support of the University of Helsinki. The Arctic-Barents Region is facing numerous pressures from a variety of sources, including the effect of environmental changes and extractive industrial developments. The threats arising out of these pressures result in human security challenges. This book analyses the formation, and promotion, of societal security within the context of the Arctic-Barents Region. It applies the human security framework, which has increasingly gained currency at the UN level since 1994 (UNDP), as a tool to provide answers to many questions that face the Barents population today. The study explores human security dimensions such as environmental security, economic security, health, food, water, energy, communities, political security and digital security in order to assess the current challenges that the Barents population experiences today or may encounter in the future. In doing so, the book develops a comprehensive analysis of vulnerabilities, challenges and needs in the Barents Region and provides recommendations for new strategies to tackle insecurity and improve the wellbeing of both indigenous and local communities. This book will be a valuable tool for academics, policy-makers and students interested in environmental and human security, sustainable development, environmental studies and the Arctic and Barents Region in particular.